2020
DOI: 10.18178/ijiet.2020.10.1.1341
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of Mobile-Assisted Language Learning for IELTS Preparation: A Case Study of Indonesian Learners

Abstract: is an M.Sc. student at the University of Bristol, UK majoring learning, technology, and society. She worked for three years at a startup Ed-Tech company which focused on online language learning. She designed e-learning concepts and managed a team during her work experiences. Since then, she has involved in Ed-Tech fields ranging from attending workshops and seminars to initiating a social project which involved online learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…This finding confirms a previous study revealing that MBA is more innovative, efficient, and thorough than others (Ningsih et al, 2022;Zubanova et al, 2021). In addition, it confirms another study highlighting that flexibility and capability of mobile phones make them valuable tools even for high stakes testing (Lestary, 2020), like university entrance test, national examination, a scholarship selection, or a license to practice a profession. In connection to its flexibility, the study reveals that Ruanguji provides tests which have better layout and appearance than paper-based tests.…”
Section: Discussionsupporting
confidence: 89%
“…This finding confirms a previous study revealing that MBA is more innovative, efficient, and thorough than others (Ningsih et al, 2022;Zubanova et al, 2021). In addition, it confirms another study highlighting that flexibility and capability of mobile phones make them valuable tools even for high stakes testing (Lestary, 2020), like university entrance test, national examination, a scholarship selection, or a license to practice a profession. In connection to its flexibility, the study reveals that Ruanguji provides tests which have better layout and appearance than paper-based tests.…”
Section: Discussionsupporting
confidence: 89%
“…To make their document eligible, the students must fulfill the standard score set by the host institutions. Lestary (2020), in her research, stated that the studies in 2017 by Tracer Study Universitas Indonesia (TSUI) and AFS Global Research Study have indicated that Indonesian youths, in particular, are motivated to be fluent in English for jobs and studying abroad purposes. It means that if any Indonesian student plans to pursue their further studies abroad, they are required to take an IELTS exam with the targeted score.…”
Section: Grammar and Listeningmentioning
confidence: 99%